The Formation of Terraces on Asteroid (101955) Bennu. Issue 4 (9th April 2022) - Barnouin, O. S.; Daly, M. G.; Seabrook, J. A.; Zhang, Y.; Thuillet, F.; Michel, P.; Roberts, J. H.; Daly, R. T.; Perry, M. E.; Susorney, H. C. M.; Jawin, E. R.; Ballouz, R.‐L.; et al.
Abstract: The surface of the rubble‐pile asteroid (101955) Bennu has been characterized in detail by the OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer) mission. By examining global and local digital terrain models, we observed that Bennu possesses terraces, that is, a series of roughly latitude‐parallel, step‐like slope breaks. These partially circumscribe the poles and extend east‐west over several longitudinal quadrants at mid‐ to high (≥30°) latitudes. The terraces are subtle in amplitude, with heights ranging from 1 to 5 m. They often exhibit back‐wasting that results in V‐shaped scarps that open downslope in some locations. When boulders >5–10 m are absent at or near a terrace, the steeper portion (the drop) of the terrace lacks rocks, whereas the flatter portion (the bench) of the terrace has accumulations of rocks at its crest. When boulders >5–10 m are present, their steep downslope faces often make up the drop from the terrace crest, and they retain debris upslope, thereby enhancing the terrace structure. A geotechnical stability analysis indicates that Bennu's surface is likely unstable and that surface cohesion is <0.6 Pa. Bennu's terraces strongly resemble scarps generated in laboratory and numerical simulations of a cohesionless granular bed as the slope of the bed increases quasi‐statically. We conclude that terraces are probably actively forming on Bennu as its surface slowly fails owing to creep induced by spin acceleration. Plain Language Summary: Analyzing the landscape of a planetary body can shed light on the processes that shape its surface over time. We used data acquired by the OSIRIS‐REx (Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer) mission to explore the rubble‐covered landscape of the near‐Earth asteroid Bennu. We observed subtle step‐like features, or terraces, no more than about 5 m in relief (about half the height of a telephone pole). These terraces are approximately parallel to lines of latitude (i.e., they run east–west) and are located in both the northern and southern hemispheres of Bennu, but not near the equator. Accumulations of rocks tend to be present at the terrace crests, and the terrace faces are usually smooth. Boulders 5–10 m in size form some terraces and enhance the terrace structure by retaining loose material upslope. Laboratory experiments and numerical simulations show that subtle terraces can form in Bennu‐like conditions if the slope of the surface increases. Thus, these landforms are evidence for the ongoing "creep" of loose material on Bennu as surface slopes change in response to the gradual acceleration in the asteroid's spin rate. Key Points: Bennu exhibits subtle latitudinal terracing at mid‐ to high latitudes Terrace surface expressions follow expectations from laboratory and numerical investigations Terraces are an expression of Bennu's current surface instability